2021
DOI: 10.3389/fphys.2021.707344
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Ameliorates Renal Ischemia-Reperfusion Injury via Inhibition of NF-κB Activation and Inflammation in Rats

Abstract: Renal ischemia-reperfusion injury (IRI) is considered as a major cause of acute kidney injury. In this study, we investigated the role of the NF-κB signaling pathway and inflammation in the amelioration of renal IRI using pioglitazone. Sprague–Dawley (SD) rats were subjected to bilateral renal artery clamping for 45 min followed by perfusion restoration for establishing a simulated renal IRI model. At 24 h post-operatively, we assessed the serum levels of creatinine and urea nitrogen, expression levels of pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Morphological changes in renal tissue were observed using an optical microscope. The degree of renal tubular necrosis was assessed according to the method described by Zou et al [ 7 ]. A maximum score of 4 indicates the highest degree of necrosis, 0 = normal kidney; 1 = minimal necrosis, <5% necrotic renal tubular involvement; 2 = mild necrosis, 5%–25% involvement; 3 = moderate necrosis, 25%–75% involvement; and 4 = severe, >75% involvement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological changes in renal tissue were observed using an optical microscope. The degree of renal tubular necrosis was assessed according to the method described by Zou et al [ 7 ]. A maximum score of 4 indicates the highest degree of necrosis, 0 = normal kidney; 1 = minimal necrosis, <5% necrotic renal tubular involvement; 2 = mild necrosis, 5%–25% involvement; 3 = moderate necrosis, 25%–75% involvement; and 4 = severe, >75% involvement.…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that the PPAR γ synthetic ligand pioglitazone exerts its renoprotective functions by inhibiting apoptosis, alleviating oxidative stress, and enhancing autophagy in in vitro and in vivo models [ 4 6 ]. Moreover, it seems that RIRI-induced inflammatory and oxidative responses are potentially ameliorated by administering pioglitazone, with inhibition of the NF- κ B signaling pathway, and alleviated renal insults in rats [ 7 ]. The crucial roles of modulating NF- κ B signaling pathway-mediated inflammation and oxidative stress in IRI have also been demonstrated by other researchers [ 8 , 9 ], which may provide a theoretical basis for the exploration of novel targets and pathways in RIRI therapy.…”
Section: Introductionmentioning
confidence: 99%
“…PPARγ agonists were reported to protect the kidney against I/R injury by inhibiting I/R injury-induced diffuse tubular necrosis and acute inflammation (Reel et al, 2013), and reducing nitric oxide plasma levels, ED-1 + cell infiltration, and cleaved caspase-3 expression (Betz et al, 2012). A recent study showed that the PPARγ agonist pioglitazone decreased the expression of NF-κB-related proteins and the mRNA expression of inflammatory cytokines, including TNF-α and monocyte chemotactic protein-1 (MCP-1) in a renal I/R model (Zou et al, 2021). These data suggest that PPARγ agonists may be helpful in reducing renal I/R injury because of their antiinflammatory, antioxidant, and anti-apoptosis effects.…”
Section: Pparγ and Acute Kidney Injurymentioning
confidence: 99%
“…Several in vivo studies demonstrated that PPAR-γ agonists can potentially alleviate I/R injury. In rats subjected to renal I/R, pioglitazone was shown to improve the histopathological and biological parameters by inhibiting the NF-κB pathway and inflammatory response [122]. In a model of myocardial I/R injury, the PPAR-γ agonist, rosiglitazone, reduced the infarct and ischemic sizes and improved the ventricular remodeling and recovery of cardiac function [123].…”
Section: Pharmacological Therapies To Modulate Metabolic Targets (Pcs...mentioning
confidence: 99%